71.0k views
2 votes
For the function f defined b f(x)=x^2+2x+3 find f(-x), -f(x), and -f(-x).

NEED HELP PLS PLS 100 PNTS

1 Answer

1 vote

Answer:

see explanation

Explanation:

To evaluate f(- x) substitute x = - x into f(x)

f(- x) = (- x)² + 2(- x) + 3 = x² - 2x + 3

-----------------------------------------------------

- f(x) = - (x² + 2x + 3) ← distribute parenthesis by - 1

= - x² - 2x - 3

-----------------------------------------------------------

- f(- x) ← substitute f(- x) from above

= - (x² - 2x + 3) ← distribute parenthesis by - 1

= - x² + 2x - 3

User Sofl
by
4.6k points